Doped antimony chalcogenide semiconductor thin films fabrication by physical vapour deposition: elucidation of optoelectronic and electrochemical features. (3rd April 2022) - Anwar, Javeria; Ahmad, Khuram Shahzad; Jaffri, Shaan Bibi; Sohail, Manzar
ABSTRACT: This work investigates the growth of low-cost barium sulphide-doped antimony sulphide by physical vapour deposition. Synthesis was done using a single-source diethyldithiocarbamate ligand as a complexation and stabilisation agent. Barium sulphide-doped antimony sulphide dithiocarbamate complexes were prepared and grown into thin films by physical vapour deposition, and were studied for crystalline, vibrational, optical, morphological and elemental composition. Stibnite orthorhombic 27 nm crystallites were detected by X-ray diffraction. Transmittance reduction resulting from augmenting absorption was expressed by vibrational analysis further confirmed by reduced bandgap for barium-doped stibnite chalcogenide thin film. Tightly packed thin films having no cracks with a thickness of 790 nm were tested for photo-electrochemical performance indicative of the remarkable photo-response shown through anodic and cathodic peaks in addition to functional stability of 1.500 ks. Electrochemistry was studied by cyclic voltammetry, linear sweep voltammetry and chronoamperometry. The profound electrochemical performance was disclosed for the synthesised sulphide thin films showing an enhancement in the current densities with increased bias potential.